Spatio-Temporal Analysis of Forest Cover Change in Halmahera and Obi Islands, Indonesia using Hansen Global Forest Change Data on Google Earth Engine - Rakuasa, Heinrich; Khromykh, Vadim V.; Rifai , Ahmat (Science Tech Group, 2025)
Forest cover change on Halmahera and Obi Islands in Indonesia is an important indicator for assessing natural resource sustainability and climate change mitigation in this biodiversity-rich tropical region. This study used Hansen Global Forest Change v1.11 data, which was processed and analyzed on the Google Earth Engine (GEE) platform, to look at how forest cover changed from 2000 to 2023, using 30-meter resolution satellite images and lossyear bands to find out the years when deforestation happened. The results of the analysis show significant deforestation trends, primarily associated with intensive nickel mining activities, leading to the loss of thousands of hectares of forest cover each year, with peaks occurring in 2015 in Halmahera and 2002 in Obi. The discussion highlights that mining activities and land conversion are major factors in forest degradation, which not only impacts local ecosystems but also contributes to global greenhouse gas emissions. The use of Hansen's data and GEE-based analysis proved effective in continuous and accurate monitoring, supporting policy-making for conservation and more sustainable management of forest resources and mitigation of the impacts of human activities in the region.